MEREPOSISI CARA PANDANG HUKUM NEGARA TERHADAP HUKUM ADAT DI INDONESIA - Sulaiman (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2017)
Adat law is still in a difficult position until now. Even adat law is marginalized, although adat law has a dynamic nature. State law has not fully considered adat law as part of its body. This article wants to understand how state law views adat law so far. Based on that perspective, repositioning is offered in view of adat law. The concept of writing is based on the law of reality perspective. The perspective of such legal studies, does not set out the concept of law in the legislation. From this writing found that from the beginning how to view custom as a law has been debated. When the colonial lawyers formulate the name of the right law related to the law of the natives. There is a process through which custom reaches the degree of law category (adat law). This debate lasted until after independence. This writing wishes to emphasize the importance of state law to change its perspective regarding the existence of adat law and indigenous peoples. Adat law should be seen as part of the body of the nation itself. Abstrak: Penelitian ini ingin memahami bagaimana hukum negara memandang hukum adat selama ini. Berdasarkan cara pandang tersebut, ditawarkan reposisi dalam memandang hukum adat. Konsep penulisan ini berbasis pada hukum perspektif realitas. Perspektif kajian hukum demikian, tidak berangkat konsep hukum dalam peraturan perundang-undangan. Dari penulisan ini ditemukan bahwa dari awal cara memandang adat sebagai hukum sudah diperdebatkan. Ketika pada ahli hukum kolonial merumuskan nama hukum yang pas terkait dengan hukum pribumi. Ada proses yang dilalui sehingga adat mencapai derajat kategori hukum (adat). Perdebatan ini berlangsung hingga usai merdeka. Penulisan ini ingin menegaskan pentingnya hukum negara mengubah cara pandangnya terkait keberadaan hukum adat dan masyarakat hukum adat. Hukum adat harus dilihat sebagai bagian dari tubuh bangsa sendiri. Kata Kunci: hukum negara; hukum adat; hukum khas Indonesia.